2
$\begingroup$

Given $z=x+iy$ and $\overline z=x-iy$, prove the following: $${\partial\over{\partial x}}={\partial\over{\partial z}}+{\partial\over{\partial{\overline z}}}$$ $$\mathbb {and}$$ $${\partial\over{\partial y}}=i\left({\partial\over{\partial z}}-{\partial\over{\partial{\overline z}}}\right)$$ I have no clue where to begin equations except that it may be related to Cauchy-Riemann equations. Any help as how to begin the proof and some hints to take note of would be of much help.

$\endgroup$
2
$\begingroup$

Let $u$ be an arbitrary continuous and differentiable function of $z$ and $\bar{z}$.

Also as $z = x+ iy$ and $\bar{z} = x-iy$,

$x = \frac{z+\bar{z}}{2}$ and $y = \frac{z-\bar{z}}{2i}$

So,

$\frac{\partial u}{\partial z} = \frac{\partial u}{\partial x}\frac{\partial x}{\partial z} + \frac{\partial u}{\partial y}\frac{\partial y}{\partial z}$

$\frac{\partial u}{\partial z} = \frac{\partial u}{\partial x}\frac{1}{2} + \frac{\partial u}{\partial y}\frac{1}{2i}$

or

$$\frac{\partial }{\partial z} = \frac{\partial }{\partial x}\frac{1}{2} - \frac{\partial }{\partial y}\frac{i}{2} \cdots(i)$$

Similarly,

$\frac{\partial u}{\partial \bar{ z}} = \frac{\partial u}{\partial x}\frac{\partial x}{\partial \bar{z}} + \frac{\partial u}{\partial y}\frac{\partial y}{\partial \bar{z}}$

$\frac{\partial u}{\partial \bar{z}} = \frac{\partial u}{\partial x}\frac{1}{2} + \frac{\partial u}{\partial y}\frac{-1}{2i}$

or $$\frac{\partial }{\partial \bar{z}} = \frac{\partial }{\partial x}\frac{1}{2} + \frac{\partial }{\partial y}\frac{i}{2}\cdots(ii)$$

Adding (i) and (ii),

$$\frac{\partial }{\partial z} + \frac{\partial }{\partial \bar{z}} = \frac{\partial }{\partial x}$$ or

$$\frac{\partial }{\partial x} = \frac{\partial }{\partial z} + \frac{\partial }{\partial \bar{z}}$$

Similarly by subtracting , we may find that

$$\frac{\partial }{\partial y} = i\big(\frac{\partial }{\partial z} - \frac{\partial }{\partial \bar{z}}\big)$$

$\endgroup$
2
$\begingroup$

$z=x+iy$ and $\overline z=x-iy$

Let $f=f(z,\overline z)$

Now ${\partial f\over{\partial x}}={\partial f\over{\partial z}} {\partial z\over{\partial{ x}}}+{\partial f\over{\partial{\overline z}}}{\partial {\overline z}\over{\partial{ x}}}={\partial f\over{\partial z}}(1)+{\partial f\over{\partial{\overline z}}}(1)=({\partial \over{\partial z}}+{\partial \over{\partial{\overline z}}})f$

$\implies{\partial\over{\partial x}}\equiv {\partial\over{\partial z}}+{\partial\over{\partial{\overline z}}}$

Similarly,

${\partial f\over{\partial y}}={\partial f\over{\partial z}} {\partial z\over{\partial{ y}}}+{\partial f\over{\partial{\overline z}}}{\partial {\overline z}\over{\partial{ y}}}={\partial f\over{\partial z}}(i)+{\partial f\over{\partial{\overline z}}}(-i)=i({\partial \over{\partial z}}-{\partial \over{\partial{\overline z}}})f$

$\implies{\partial\over{\partial y}}\equiv i({\partial\over{\partial z}}-{\partial\over{\partial{\overline z}}})$

$\endgroup$
2
$\begingroup$

$dz$ = $dx+ i dy$, $d \bar z = dx - i dy$

By definition, $\partial_z$ is such a combination of $\partial_x$ and $\partial_y$ that $dz(\partial_z) = 1$

Let's check if $\partial_z = (\partial_x - i\partial_y)/2$ fits.

$dx((\partial_x - i\partial_y)/2)+ idy((\partial_x - i\partial_y)/2) = \frac{1}{2} dx(\partial_x) + \frac{1}{2} idy(-i \partial_y) = 1$.

The same way you check that $\partial_{\bar{z}} = (\partial_x - i \partial_y) /2$

Dealing with the differentials is simple, because you can transform one differential into sum of others fast, but the vector fields are a bit harder to operate so I use duality between differential forms and vector fields. Since this duality is one-to-one, it's sufficient just to check that the equality holds.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.